Engraftable neural crest stem cells derived from cynomolgus monkey embryonic stem cells. (January 2015) - Li, Weiqiang; Huang, Lihua; Lin, Wanyi; Ke, Qiong; Chen, Rui; Lai, Xingqiang; Wang, Xiaoyu; Zhang, Jifeng; Jiang, Meihua; Huang, Weijun; Wang, Tao; Yang, Xuesong; et al.
Abstract: Neural crest stem cells (NCSCs), a population of multipotent cells that migrate extensively and give rise to diverse derivatives, including peripheral and enteric neurons and glia, craniofacial cartilage and bone, melanocytes and smooth muscle, have great potential for regenerative medicine. Non-human primates provide optimal models for the development of stem cell therapies. Here, we describe the first derivation of NCSCs from cynomolgus monkey embryonic stem cells (CmESCs) at the neural rosette stage. CmESC-derived neurospheres replated on polyornithine/laminin-coated dishes migrated onto the substrate and showed characteristic expression of NCSC markers, including Sox10, AP2α, Slug, Nestin, p75, and HNK1. CmNCSCs were capable of propagating in an undifferentiated state in vitro as adherent or suspension cultures, and could be subsequently induced to differentiate towards peripheral nervous system lineages (peripheral sympathetic neurons, sensory neurons, and Schwann cells) and mesenchymal lineages (osteoblasts, adipocytes, chondrocytes, and smooth muscle cells). CmNCSCs transplanted into developing chick embryos or fetal brains of cynomolgus macaques survived, migrated, and differentiated into progeny consistent with a neural crest identity. Our studies demonstrate that CmNCSCs offer a new tool for investigating neural crest development and neural crest-associated human disease and suggest that this non-human primate model may facilitate tissue engineering and regenerative medicine efforts.